MENUMBUHKAN MINAT KEWIRAUSAHAAN DENGAN PELATIHAN KEWIRAUSAHAAN (BUSINESS MODEL CANVAS DAN BUSINESS PLAN) DI BIDANG KIMIA INDUSTRI DI SMK SWASTA SATRYA BUDI 1 PERDAGANGAN - Gustina Siregar; Yudha Andriansyah Putra; Lila Bismala; Hafsah Hafsah; Dewi Andriany; Susi Handayani; Mutia Arda; Lailan Safina Hasibuan (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Entrepreneurship is seen as an important activity in the economy, so it must be introduced and instilled from an early age at all levels of education. This activity was carried out with the aim of increasing entrepreneurial interest in vocational school students, improving their ability to create business ideas, business opportunities, and the ability to compile BMCs and business plans. The Business Model Canvas document and business plan are very important to explain the business, projections, opportunities and challenges faced. The method used is training, using experiential learning, which emphasizes the active involvement of participants in the learning process through direct experience, discussion, reflection, and feedback. The active participation of training participants is essential for the success of the training. After providing the material, participants were divided into groups to determine business ideas and then compile a BMC and business plan.  The training ran smoothly, participants understood the material presented, were able to find business ideas, business opportunities and were able to compile BMC and business plans. The training ran smoothly, participants understood the material presented, were able to find business ideas, business opportunities and were able to compile BMC and business plans.